Crimean-Congo haemorrhagic fever virus in Hyalomma impeltatum ticks from North Kordofan, the Sudan - Lidia Chitimia-Dobler; Makarim Habeeb Issa; Malaz Esamalden Ezalden; Idris Ahmed Yagoub; Mohamed Abdalsalam Abdalla; Amel Omer Bakhiet; Sabine Schaper; Ramona Rieß; Patrick Vollmar; Anne Grumbach; Malena Bestehorn; Markus Antwerpen; et al. (International Journal of Infectious Diseases, 2019)
An evidence for Crimean-Congo hemorrhagic fever virus (CCHFV) was found in Hyalomma impeltatum ticks collected from sheep in North Kordofan in the Sudan. Based on sequencing of the partial segment S, the detected virus belongs to lineage I with closest similarity to CCHFV strains from Senegal. So far, this lineage is unknown in the Sudan. Keywords: Hyalomma ticks, Crimean-Congo hemorrhagic fever virus, Sheep, Sudan